S stvarmi do ljudi - Jurančič Šribar, Luna (Etnolog. Nova vrsta (Ljubljana), 2010)
The article addresses alternative forms of empowering people with an experience of homelessness by establishing equal relations of exchange betweenthem and the wider society. It is based on fieldwork among the homeless of the 'Kings of the Street' Association (Društvo Kralji ulice) and a joint socio-environmental project, aimed at establishing a local community that will not be based on the prevalent market economy relations.
Keywords: Slovenci; Slovenes; brezdomstvo; brezdomci; association; društva; Kralji ulice; družbena izključenost